Social Learning of Company’s Personnel by Means of Cloud Decisions - Svetlana Akhmetova; Larisa Nevskaya; Marina Akhmetova (Montenegrin Journal of Economics)
New tendencies of personnel training in conditions of partial company’s budget on the base of formal and infoprmal components use have been described in the article. The main social training instruments have been characterized. The review of experience of foreign companies which successfully apply the instruments of social personnel learning has been given. It has been proposed new model of social learning based on the application of cloud decisions and learning platform.